Early Death in Two Patients with Acute Promyelocytic Leukemia Presenting the bcr3 Isoform, FLT3-ITD Mutation, and Elevated WT1 Level. (7th July 2013) - Greco, Marianna; Caocci, Giovanni; Ledda, Antonio; Vacca, Adriana; Arras, Marcella; Celeghini, Ivana; La Nasa, Giorgio
Abstract : Despite major advances in the treatment of acute promyelocytic leukemia (APL), the problem of early death (ED) remains unsolved. Alongside the currently known clinical and hematological risk factors, prognostic significance has been attributed to internal tandem duplication mutations of the fms-like tyrosine kinase-3 (FLT3-ITD), hypogranular variant morphology, and the bcr-3 isoform of PML-RAR α . We describe premature death of two patients with the hypogranular variant of APL who presented remarkably high expression levels of Wilms' tumor gene (WT1). Our results point to WT1 as an important prognostic factor of ED that needs to be promptly evaluated in all newly diagnosed cases of APL.